The Level of Indoor Thermal Comfort in Malaysian Student Residential College - Nur Syahirah Nissa Khamis; Shareh Musa, Sharifah Meryam; Manap, Manap; Kasim, Narimah; Zainal, Rozlin (International Journal of Sustainable Construction Engineering and Technology, 2022)
Higher education institutions (HEI) are the centre of learning and teaching that are responsible for producing high-quality first-generation. The inadequate number of student accommodations also resulted in stacking several students in one room, leading to discomfort, space constraints, lack of privacy, and other health conditions. This study investigates the level of indoor thermal comfort on occupant living at student residential college, which was built by the private party without complying with the design elements that have been gazette by Malaysian building standard. Besides that, the relationship between the room orientation designs in influencing student comfort level will also be inspected. The method consisted of distributing a questionnaire to the occupants and measuring operative air temperature. The study results found that the respondents have a high level of dependence on the mechanical ventilation system, namely the fan, due to the higher temperature and lack of airflow elements. This study also shows a positive relationship between the room orientation designs affecting the level of comfort of the occupants, supported by a correlation analysis. High average temperature occurs at the peak hour (noon) recorded at 31°C, which is above the recommended standard temperature listed by the Department of Standard Malaysia. This study help increase the knowledge of indoor thermal comfort throughout the design phase that can maximize the occupant’s wellbeing and productivity.